Size Dependent Photocatalytic Activity of ZnO Nanosheets for Degradation of Methyl Red - Aljaafari, Abdullah (Frontiers in Materials, 2020)
In this work, ZnO nanosheets with a tunable thickness were produced by microwave-assisted hydrothermal based method. The product was well characterized by various tools such as XRD, SEM, EDX spectroscopy, TEM, and Raman spectroscopy. ZnO nanosheets were highly crystalline and possessed single phase with the wurtzite structure. The ZnO nanosheets have thickness ranging from 20 to 50 nm, as shown by the micrographs of SEM. The SAED pattern infered that the ZnO nanosheets have single crystal nature with preferential growth direction along [0001]. ZnO nanosheets with E2high mode of wurtzite structure was observed by Raman scattering spectra. The photodegradation of methyl red using ZnO nanosheets was measured under UV light irradiation. In comparison with the commercial ZnO, ZnO nanosheets showed higher efficiency in photodegradation of organic dyes. The thinner the nanosheets, the higher their performance, which can be explained based on surface area. The excellent performance of ZnO nanosheets in photodegradable organic dyes might be important in environmental treatment and photocatalysis applications.